Strain sensitivity as selection criterion for elastic elements of force transducers: a brief review - Ştefănescu, Dan Mihai (Sensors and actuators. A. Physical., 2020)
[Display omitted] •Extended classification of force transducers elastic elements, showing their ranges (in newtons) and strain sensitivities.•Global sensitivity (mechanical + electrical) defined in terms of three parameters (ε– strain, k – gauge factor and n– bridge factor).•Colour code systematic representation of the strain gauges location on elastic elements and their connection in Wheatstone bridge. What does a researcher, a student or a technician make when facing a special measurement application and no adequate force transducer (FT) is available on the market? He could attempt a personal solution (customization), based on the widespread sensors, namely strain gauges (SGs), bonded on one of the elastic elements (EEs) presented in this work and then connecting them in a Wheatstone bridge so that to get a maximal Strain Sensitivity. Further, if time and skill allows, he may also try Optimal Shape Design for more special EEs, adding a contribution to strain gauge measurements advancement or, shortly, tensometry. In this paper the most complete classification of elastic elements is presented, based on 12 relevant types, showing both the mechanical sensitivity (by optimally locating of SGs) and the electrical one (by their connection in a Wheatstone bridge), as well as the Force range (expressed in newtons) for each type. This inter- and multi-disciplinary subject is illustrated by three examples of high performance EEs for SGFTs computer aided design, with pictures suggesting too a unitary representation of various mechanical stresses (stretching, bending, shearing) “instrumented” by using Wheatstone bridges. Within this “scientific story” it might be useful for readers to consider the Strain Sensitivity criterion when selecting EEs for SGFTs for applications involving high measurement accuracy (force comparison standards, multicomponent force-moment applications in Robotics and aerodynamic balances for aircraft or vehicle models in wind tunnels).